Road construction method and road structure
Patent Information
- Application Number
- JP2023147615
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-06-12
AI Technical Summary
Existing waterproof materials for multi-story parking lots and rooftop parking lots suffer from cracking, peeling, and poor weather resistance due to repeated vehicle stress, especially when vehicles with chains are driven during snowfall, and conventional hard urethane cement materials exhibit curing shrinkage and inadequate weather resistance.
A road surface construction method and structure that includes a waterproof layer followed by a protective layer using a water-based hard urethane cement material with a high ratio of aliphatic isocyanate resin, which minimizes curing shrinkage and enhances weather resistance.
The method and structure provide durability against vehicle stress, reduce curing shrinkage, and maintain excellent weather resistance, preventing cracking and peeling, even under harsh conditions.
Abstract
Description
[Technical Field]
[0001] The present invention relates to a road surface construction method and road surface structure, primarily for parking lots, which are particularly suitable for use in multi-story parking garages. [Background technology]
[0002] Traditionally, waterproofing materials have been applied to the top of structures to protect them from wind and rain. Examples of waterproofing materials include acrylic rubber coating waterproofing, urethane rubber coating waterproofing, FRP waterproofing, asphalt waterproofing, PVC sheet waterproofing, synthetic rubber sheet waterproofing, and polymer cement waterproofing. The appropriate waterproofing material is selected depending on the type of structure and the environment in which it is used.
[0003] Furthermore, in urban areas where parking is scarce, department stores, mass retailers, theaters, restaurants, and other establishments sometimes use the rooftops of structures as parking lots to secure more parking spaces. Waterproofing materials used on the road surfaces of these rooftop parking lots and parking lots known as multi-story parking lots (in this specification and the present invention, all floor surfaces including vehicle driving paths and parking spaces in a parking lot are referred to as "parking lot road surfaces" or "parking lot road surfaces") are required to not only maintain waterproofing performance that prevents rainwater and the like from entering the interior for a long period of time, but also to possess durability against vehicle traffic, abrasion resistance, ultraviolet rays, acid rain, wind and snow, etc.
[0004] Hereafter, in this specification, parking facilities that are installed outdoors or semi-outdoors where vehicles travel and that require waterproofing functions, such as rooftop parking lots and multi-story parking garages, will be collectively referred to as "multi-story parking garages." Furthermore, in this invention, the concept of "parking facility" also includes places where vehicles may be temporarily parked, even if parking is not the primary purpose (for example, car washes, gas stations, charging stations, the floor of car ferries, etc.), and roadways (ramps, etc.) leading to parking facilities.
[0005] For waterproofing materials used in multi-story parking garages, a construction method is employed that uses a hard material on the surface to withstand vehicle traffic. One example of this method is urethane material, which is composed of multiple layers of urethane. The first layer facing the substrate uses a soft urethane material to cushion the movement of the substrate and follow cracks. The second layer forms a layer that is slightly harder than the first layer, and the third layer on top is a high-strength urethane layer, creating a waterproofing system that can withstand abrasion and peeling caused by vehicle traffic.
[0006] However, even in parking lot surfaces where rigid polyurethane material is used as the surface layer, repeated vehicle traffic and stress from turning tires while parking can cause cracks and delamination in the waterproofing material. In particular, problems are often observed to occur early when vehicles are driven on the surface with snow chains attached during snowfall. Similar phenomena may also occur in parking lot surfaces using other waterproofing materials.
[0007] On the other hand, water-based rigid urethane cement materials are used as flooring materials with excellent durability (see, for example, Patent Documents 1 and 2). This material is composed of polyol resin, isocyanate resin, hydraulic cement, aggregate, pigment, water, etc., and a three-dimensional structure is formed by the simultaneous hydration reaction between hydraulic cement and water, urethane bonding through the reaction of hydroxyl groups and isocyanate groups, and urea bonding through the reaction of isocyanate groups and water. These materials are mixed and used before application. The cured coating is hard and has excellent abrasion resistance, heat resistance, and chemical resistance, so it is used for floors in food factories and machine factories. Polyisocyanate resins mainly used are 4,4'-diphenylmethane diisocyanate (MDI) and polyphenyl isocyanate (polymeric MDI), which have good curing speed and heat resistance.
[0008] Even when such highly durable flooring materials are used on the surface of multi-story parking garages where vehicles drive, repeated vehicle traffic and stress from turning tires while parking can still cause cracks and delamination in the waterproofing material. In particular, problems are often observed to occur prematurely when vehicles are driven on the road with snow chains attached during snowfall.
[0009] In addition, aqueous rigid urethane-based cement materials using 4,4'-diphenylmethane diisocyanate (MDI) or polyphenyl isocyanate (polymeric MDI) are excellent in durability against vehicle running, but when they are applied on a soft waterproof material with large curing shrinkage, warping may occur due to the curing shrinkage. Further, since the weather resistance is not sufficient and discoloration occurs relatively early, it is not suitable for outdoor applications.
Prior Art Documents
Patent Documents
[0010]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0011] Therefore, the present invention has been made to solve the above-described problems, and has durability against repeated vehicle running, tire setting when parking, and vehicle running with chains attached during snowfall, and is capable of forming a hard protective layer with little curing shrinkage and excellent weather resistance. An object of the present invention is to provide a road surface construction method and a road surface structure.
Means for Solving the Problems
[0012] The above object is solved by the following present invention.
[0013] That is, the road surface construction method of the present invention is a waterproof layer forming step of forming, on a road surface base, any waterproof layer selected from the group consisting of an acrylic rubber coating waterproof layer, a urethane rubber coating waterproof layer, a vinyl chloride sheet waterproof layer, and a synthetic rubber sheet waterproof layer, which has waterproof properties; A protective layer forming step of forming a hard protective layer as an upper layer of the waterproof layer directly or through an adhesive layer using an aqueous hard urethane-based cement material containing at least a polyol resin, an isocyanate resin, and a hydraulic cement; It has, and the ratio of the aliphatic isocyanate resin to all the isocyanate resins contained in the aqueous hard urethane-based cement material is 0.5 or more in terms of NCO equivalent ratio. In the method for constructing a road surface of the present invention, there is no particular limitation on the waterproof layer forming step, but the step of supplying a liquid waterproof material to the road surface base and curing it to form the waterproof layer is a preferred embodiment in terms of workability.
[0014] On the other hand, the road surface structure of the present invention A waterproof layer formed on the road surface base, having waterproof properties, and selected from the group consisting of an acrylic rubber coating waterproof layer, a urethane rubber coating waterproof layer, a PVC sheet waterproof layer, and a synthetic rubber sheet waterproof layer; A hard protective layer made of an aqueous hard urethane-based cement material laminated directly or through an adhesive layer as an upper layer of the waterproof layer; It consists of, and the ratio of the aliphatic isocyanate resin to all the isocyanate resins contained in the aqueous hard urethane-based cement material is 0.5 or more in terms of NCO equivalent ratio. In the road surface structure of the present invention, there is no particular limitation on the waterproof layer, and it only needs to have adhesiveness to the upper hard protective layer. However, making it a layer obtained by curing a liquid waterproof material is a preferred embodiment in terms of workability.
Effects of the Invention
[0015] According to the present invention, it is possible to provide a method for constructing a road surface and a road surface structure in which a hard protective layer having durability against repeated vehicle running, tire setting when parking, and vehicle running with chains attached during snowfall, and having little curing shrinkage and excellent weather resistance is formed.
Embodiments for Carrying Out the Invention
[0016] The following will first describe the road surface construction method of the present invention, and then describe the road surface structure of the present invention. The water-based rigid urethane cement material for road surfaces will be described as "a water-based rigid urethane cement material characteristic of the present invention" within the road surface construction method of the present invention. [The present invention's method for constructing road surfaces] The road surface construction method of the present invention comprises a waterproof layer formation step and a protective layer formation step.
[0017] <Waterproof layer formation process> In the present invention, the waterproof layer formation step is the step of forming a waterproof layer having waterproof properties on a road surface substrate. The formed waterproof layer is made of a waterproof material that has the ability to prevent rainwater from entering structures, etc. (waterproof performance).
[0018] The road surface substrate refers to the flat surface area (including slopes such as ramps; the same applies hereinafter when referring to the "flat surface area") of a structure intended for use as a multi-story parking garage or rooftop parking garage, and is a floor surface that has been poured with concrete or paved with asphalt. To improve adhesion with the waterproofing layer, the road surface substrate may be roughened or an adhesive layer may be applied using a primer or adhesive. In this invention, the term "road surface substrate" is not limited to structures, but broadly refers to the flat surface area intended for use as a road surface, such as a parking garage.
[0019] The waterproofing material used to form the waterproofing layer is not particularly limited; any material that adheres to the material forming the upper layer (protective layer) (a water-based rigid urethane cement material, as described later) can be used. However, a material that can form a layer capable of following cracks that occur in the underlying road surface and the expansion and contraction of the structure is preferred.
[0020] In this invention, the term "waterproofing material" refers to a substance in a liquid state, dispersion, viscosity, or gel state (all of which are included in the concept of "liquid" in this invention), which forms a waterproofing layer when supplied to a road surface and allowed to harden (hereinafter referred to as "liquid waterproofing agent"), and a sheet-like material that forms a waterproofing layer when attached to a road surface substrate (hereinafter referred to as "sheet-type waterproofing material").
[0021] Examples of waterproofing layers that can be formed include waterproofing layers formed by supplying liquid waterproofing agents to the road surface substrate and allowing them to harden, such as acrylic rubber coating waterproofing layers, urethane rubber coating waterproofing layers, FRP (fiber-reinforced resin) coating waterproofing layers, polymer cement waterproofing layers, and asphalt waterproofing layers, as well as waterproofing layers formed by attaching waterproof sheet-like waterproofing materials to the road surface substrate, such as PVC sheet waterproofing layers and synthetic rubber sheet waterproofing layers. From the standpoint of ease of application, a waterproof layer formed by supplying a liquid waterproofing agent to the road surface substrate and allowing it to harden is preferred. Among these, acrylic rubber coating waterproof layers, urethane rubber coating waterproof layers, and polymer cement waterproof layers are more preferred in terms of adhesion to the upper layer (protective layer).
[0022] Examples of waterproofing materials used to form an acrylic rubber coating waterproof layer include acrylic rubber-based materials specified in JIS A 6021 "Waterproofing Materials for Buildings". Specific examples of waterproofing materials used to form an acrylic rubber coating waterproof layer include AtomRaise JS manufactured by Atomix Co., Ltd.
[0023] Examples of waterproofing materials used to form a urethane rubber coating waterproof layer include urethane rubber-based materials specified in JIS A 6021 "Waterproofing Materials for Buildings". Specific examples of waterproofing materials used to form a urethane rubber coating waterproof layer include Atrane U-60 Super manufactured by Atomix Co., Ltd.
[0024] The waterproofing material that forms the polymer cement waterproofing layer consists of a soft acrylic resin or rubber resin with a glass transition temperature (Tg) of 10°C or lower, cement, and aggregate. Specific examples of waterproofing materials that form the polymer cement waterproofing layer include, for example, Substrate Adjustment Material A manufactured by Atomix Co., Ltd.
[0025] If the waterproofing layer formation process involves supplying a liquid waterproofing agent to the road surface substrate and allowing it to harden to form a waterproofing layer, then the waterproofing layer should be formed by supplying the liquid waterproofing agent to the road surface substrate using an appropriate method according to the type of liquid waterproofing agent used and allowing it to harden. The method of supplying the waterproofing material to the road surface substrate should follow the general methods of applying road marking paint to road surfaces or general methods of applying asphalt, such as brush application, trowel application, or roller application.
[0026] When the waterproofing layer formation process involves supplying a liquid waterproofing agent to the road surface substrate and allowing it to harden to form a waterproofing layer, the amount of liquid waterproofing agent to be supplied to the road surface substrate cannot be generalized as it depends on the type of liquid waterproofing agent. However, in order to secure the desired thickness as described later, for example, with urethane rubber coating waterproofing material, 1.0 kg / m 2 ~5.0g / m 2 It is preferable that it be within a certain range.
[0027] Methods for curing liquid waterproofing agents supplied to road surface substrates include leaving them to harden naturally, and the appropriate method should be selected depending on the waterproofing material used. On the other hand, if the waterproofing layer formation process involves forming a waterproofing layer by attaching a sheet-like waterproofing material to the road surface substrate, then the sheet-like waterproofing material can be directly attached to the road surface substrate with an adhesive.
[0028] In the waterproofing layer formation process, after supplying liquid waterproofing agent to the road surface substrate, reinforcing materials are placed, and then more liquid waterproofing agent is supplied on top of the reinforcing materials. By curing the entire structure, the waterproofing layer can be given strength and durability. Various fibers, fabrics, nonwoven fabrics, etc., can be used as reinforcing materials.
[0029] In particular, reinforcing materials in the form of fabric, such as woven or nonwoven fabrics, are preferable because they provide high strength and durability, and allow for simple installation by simply attaching them to the road surface to which the liquid waterproofing agent has been supplied. Specific examples of such reinforcing materials include, for example, Volance (nonwoven fabric) manufactured by Atomix Co., Ltd.
[0030] Furthermore, in order to ensure sufficient thickness or to improve performance, the waterproof layer formation process described above may be repeated two or more times to form a multi-layered waterproof layer. In this case, waterproof layers of the same configuration may be formed on top of each other, or waterproof layers of different configurations may be formed on top of each other.
[0031] <Protective layer formation process> In the present invention, the protective layer formation step is a step of forming a hard protective layer using a water-based hard urethane cement material characteristic of the present invention. First, the water-based hard urethane cement material characteristic of the present invention will be described, and then the method for forming the hard protective layer in the protective layer formation step will be described.
[0032] (Water-based rigid polyurethane cement material) The aqueous rigid urethane cement material characteristic of the present invention contains at least a polyol resin, an isocyanate resin, and a hydraulic cement as essential components, and also contains aggregate, pigment, hardening accelerator, additives, water, etc., as needed.
[0033] Polyol resins are resin compounds having two or more hydroxyl groups in one molecule. Examples of usable polyol resins include polyhydric alcohols, polyether polyols, polyester polyols, acrylic polyols, castor oil or its derivatives, and polybutadiene polyols.
[0034] In the present invention, polyether polyols, polyester polyols, castor oil, or derivatives thereof are preferred as polyol resins from the viewpoint of reactivity and the performance of the cured product. These polyol resins may be used individually or mixed as appropriate.
[0035] Isocyanate resins are compounds having two or more isocyanate groups in one molecule. Usable isocyanate resins include aliphatic isocyanates such as hexamethylene diisocyanate, alicyclic diisocyanates such as 4,4'-dicyclohexylmethane diisocyanate (hydrogenated MDI) and isophorone diisocyanate, aromatic isocyanates such as tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), polymeric MDI, and xylylene diisocyanate, as well as nurates and bilets obtained by modifying these compounds to form trimer structures, and their derivatives and reactants.
[0036] Among these, due to their characteristics such as low curing shrinkage and excellent weather resistance, the present invention uses aliphatic isocyanates such as hexamethylene diisocyanate, as well as nurates and bilets obtained by modifying these compounds to form trimer structures, and their derivatives and reactants (collectively referred to as "aliphatic isocyanate resins" in the present invention).
[0037] However, other isocyanate resins may be used in combination, provided that they do not impair the low shrinkage and weather resistance desired for the hard protective layer in this invention. The ratio of aliphatic isocyanate resin is required to be 0.5 or higher in terms of NCO equivalent ratio, preferably 0.7 or higher, and more preferably 0.8 or higher. In particular, if the ratio of aromatic isocyanate exceeds 0.5, there is a concern that curing shrinkage will increase and weather resistance will decrease. For this reason, aliphatic isocyanate resin is used primarily (in this invention, "primarily" means more than half of the total isocyanate resin in terms of NCO equivalent ratio).
[0038] The mixing ratio of polyol resin and isocyanate resin is designed based on the curing speed and the required properties of the cured product. The ratio of moles of isocyanate groups to total hydroxyl groups (isocyanate groups / hydroxyl groups) is preferably in the range of 0.8 to 4.0, and more preferably in the range of 1.0 to 3.0.
[0039] Examples of hydraulic cements that can be used in the water-based rigid urethane cement material characteristic of the present invention include Portland cement, white Portland cement, blast furnace cement, fly ash cement, and rapid-hardening cement, which can be used individually or in mixtures. There are no particular restrictions on which cements can be used, but if it is desired to use the water-based rigid urethane cement material with color, white Portland cement, which does not inhibit the color development of the coloring pigment, is preferably used.
[0040] In the aqueous rigid urethane cement material characteristic of the present invention, the mixing ratio of hydraulic cement to total resin (total amount of polyol resin and isocyanate resin) is preferably in the range of 0.8 to 2.2 by mass, more preferably in the range of 1.2 to 2.0, and even more preferably in the range of 1.4 to 1.8. If the mixing ratio of hydraulic cement is too low, it is difficult to obtain sufficient strength in the hardened product, and conversely, if it is too high, the viscosity of the material increases, reducing workability and adhesion to the substrate, so both are undesirable.
[0041] The aqueous rigid urethane cement material characteristic of the present invention may contain aggregate. The inclusion of aggregate is preferable because it improves dimensional stability and slip resistance. Usable aggregates include crushed natural siliceous compounds such as silica sand and river sand, and crushed inorganic compounds such as glass, ceramics, fused alumina, silicon carbide, insulators, and porcelain. Hollow materials such as glass balloons and shirasu balloons can also be used.
[0042] In the aqueous rigid urethane cement material characteristic of the present invention, the aggregate particle size is preferably in the range of 0.1 to 3.0 mm. The aggregate content in the aqueous rigid urethane cement material characteristic of the present invention is preferably in the range of 60 to 80 parts by mass per 100 parts by mass of hydraulic cement. If the aggregate content is too low, dimensional stability decreases and it becomes difficult to obtain sufficient anti-slip performance, while if it is too high, the viscosity of the material increases, workability decreases and adhesion to the substrate tends to decrease, so both are undesirable.
[0043] The aqueous rigid urethane cement material characteristic of the present invention may contain pigments. Usable pigments include coloring pigments and extender pigments. Coloring pigments can be those commonly used to color paints, and are not particularly limited as long as they do not inhibit the hardening properties of the aqueous rigid urethane cement material. Usable coloring pigments include, for example, various coloring pigments and toners such as titanium dioxide, inorganic pigments such as lead yellow and iron oxide, and organic pigments such as azo pigments and phthalocyanine pigments. On the other hand, usable extender pigments include calcium carbonate, calcium hydroxide, talc, and precipitated barium sulfate.
[0044] The aqueous rigid urethane cement material characteristic of the present invention may contain a urethane resin curing accelerator (hereinafter sometimes simply referred to as "curing accelerator"). The curing accelerator is used to promote the reaction between the hydroxyl groups of the polyol resin and the isocyanate groups of the isocyanate resin.
[0045] Examples of usable hardening accelerators include tertiary amines such as 2,4,6-tris(dimethylaminomethyl)phenol and 2(dimethylaminomethyl)phenol, and organotin compounds such as dibutyltin dilaurate and dibutyltin diacetate. However, the hardening accelerator is not limited to these, as long as it does not inhibit the hydration reaction of the hydraulic cement; various hardening accelerators can be used.
[0046] The amount of curing accelerator to be added varies depending on the type of curing accelerator and the conditions of use, so it is not possible to give a general answer. An appropriate amount should be selected based on publicly available knowledge, but generally, it is selected from a range of 0.1% to 3.0% by mass relative to the total amount of resin (sum of polyol resin and isocyanate resin).
[0047] The water-based rigid urethane cement material characteristic of the present invention can be further compounded with additives. Examples of usable additives include cement water-reducing agents and defoaming agents. Cement water-reducing agents improve the dispersion of hydraulic cement and aggregate, as well as the miscibility with resins, thereby improving dispersion stability and fluidity. Examples of usable cement water-reducing agents include phthalate-based, naphthalene sulfonic acid-based, polycarboxylic acid-based, and lignin sulfonic acid-based agents.
[0048] Defoaming agents are added to water-based rigid urethane cement materials to prevent air bubbles from remaining in the hardened product, thereby improving the performance of the hardened product and the workability of the application process. Examples of usable defoaming agents include mineral oil-based and silicone-based defoaming agents.
[0049] The aqueous rigid urethane cement material characteristic of the present invention may contain components other than those listed above. Examples of other components that can be added include plasticizers. Examples of possible plasticizers include, but are not limited to, dioctyl phthalate, diisononyl phthalate, dioctyl adipate, and glycol benzoate.
[0050] The water-based rigid urethane cement material characteristic of the present invention contains water. The water-cement ratio is determined based on the type of hydraulic cement used, workability, and physical properties of the hardened product. The water-cement ratio is expressed by mass and is preferably in the range of 0.5 to 3.0, and more preferably in the range of 1.0 to 2.0.
[0051] (Method for forming a hard protective layer) In the protective layer formation process, the method for forming the hard protective layer is to supply the water-based hard urethane cement material, which is characteristic of the present invention as described above, to the surface of the waterproof layer formed on the road surface in the waterproof layer formation process and allow it to harden.
[0052] The method for supplying water-based rigid urethane cement material onto a road surface with a waterproof layer can follow the general application methods for road marking paints or general construction methods for asphalt, such as brush application, trowel application, or roller application. The amount of water-based rigid polyurethane cement material to be supplied to the road surface where the waterproof layer is formed cannot be stated definitively as it depends on the composition of the water-based rigid polyurethane cement material, but in order to ensure the desired thickness as described later, 5 kg / m 2 ~20kg / m 2 It is preferable that it be within a certain range.
[0053] For curing the water-based rigid urethane cement material supplied onto a road surface with a waterproof layer, it is acceptable to leave it to harden naturally, but it may also be actively hardened by applying heat. Depending on the waterproofing material used, it is also possible to supply the water-based rigid urethane cement material without hardening the liquid waterproofing agent supplied in the waterproof layer formation process, thereby hardening the waterproof layer and the rigid protective layer simultaneously.
[0054] Furthermore, the protective layer formation process described above may be repeated two or more times to form a multi-layered hard protective layer. In this case, hard protective layers with the same configuration may be formed on top of each other, or hard protective layers with different configurations may be formed on top of each other.
[0055] <Other processes> In the present invention, in order to ensure adhesion between the waterproof layer and the hard protective layer, an adhesive layer formation step may be included between the waterproof layer formation step and the protective layer formation step, in which a thin adhesive layer such as a primer or adhesive is formed between the two layers. The adhesive layer formation step is a step of applying a primer or adhesive to the road surface on which the waterproof layer has been formed, and may be cured before the protective layer formation step if necessary.
[0056] Furthermore, in the present invention, a topcoat forming step may be added to the road surface after the hard protective layer has been formed in the protective layer forming step, in order to further improve weather resistance and stain resistance. The topcoat layer formed by the topcoat agent is preferably a thin film.
[0057] [Road surface structure of the present invention] The road surface structure of the present invention is characterized by comprising a waterproof layer having waterproof properties formed on a road surface substrate, and a hard protective layer made of a water-based rigid urethane cement material laminated as an upper layer of the waterproof layer.
[0058] The road surface structure of the present invention is broadly divided into two layers. The lower layer is a waterproof layer that has the performance to prevent rainwater and other elements from entering the structure (waterproof performance), and the upper layer is a hard protective layer that has durability against repeated vehicle traffic, turning of tires when parked, and vehicle traffic with snow chains attached during snowfall.
[0059] Examples of waterproofing layers include those formed by supplying liquid waterproofing agents to the road surface substrate and allowing them to harden, such as acrylic rubber coating waterproofing layers, urethane rubber coating waterproofing layers, FRP (fiber-reinforced resin) coating waterproofing layers, polymer cement waterproofing layers, and asphalt waterproofing layers, as well as those formed by attaching waterproof sheet-like waterproofing materials to the road surface substrate, such as PVC sheet waterproofing layers and synthetic rubber sheet waterproofing layers.
[0060] From the standpoint of ease of application, a waterproof layer formed by supplying a liquid waterproofing agent to the road surface substrate and allowing it to harden is preferred. Among these, acrylic rubber coating waterproof layers, urethane rubber coating waterproof layers, and polymer cement waterproof layers are more preferred in terms of adhesion to the upper layer (protective layer).
[0061] The waterproof layer can be formed by the method described in the "Waterproof Layer Formation Process" section of "The Road Surface Construction Method of the Present Invention." The waterproof layer may be a multi-layer structure formed by stacking waterproof layers of the same or different configurations, either to ensure sufficient thickness or to improve performance. In this invention, even if the waterproof layer has a multi-layer structure, it will be treated as a single waterproof layer as a whole.
[0062] The ideal thickness of the waterproofing layer cannot be generalized as it depends on the type of waterproofing material. A suitable thickness should be selected from a wide range of approximately 0.5mm to 20mm, depending on the material. For example, with urethane rubber coating waterproofing materials, a thickness of 1mm to 4mm is preferable to ensure reliable waterproofing. While 3mm to 4mm is also acceptable, from an economic standpoint, a thickness of 2mm to 3mm is more practical.
[0063] The hard protective layer is formed by the "water-based hard urethane cement material characteristic of the present invention" as described in the section "Method for constructing road surfaces of the present invention." Specifically, the water-based hard urethane cement material is supplied onto the road surface of a parking lot or the like on which the waterproof layer has been formed, and then hardened to form the protective layer.
[0064] The hard protective layer can be formed by the method described in the "Protective Layer Formation Process" section of the "Road Surface Construction Method of the Present Invention." The hard protective layer may be a multi-layer structure formed by stacking hard protective layers of the same or different configurations, either to ensure sufficient thickness or to improve performance. In this invention, even if the hard protective layer has a multi-layer structure, it will be treated as a single hard protective layer as a whole.
[0065] The thickness of the hard protective layer cannot be generalized as it depends on the composition of the water-based hard urethane cement material used, but to ensure durability, it is preferable to have a thickness in the range of 3 mm to 10 mm, and more preferably in the range of 6 mm to 8 mm.
[0066] In the road surface structure of the present invention, an adhesive layer may be provided between the waterproof layer and the hard protective layer to enhance the adhesion between the two layers. The adhesive layer can be formed using conventionally known primers or adhesives. The thickness of the adhesive layer can be appropriately selected depending on the primer or adhesive used, but it is desirable that the thickness be such that it does not impair the durability of the road surface structure of the present invention, so a thin film is preferred, and specifically selected from a range of about 20 μm to 200 μm.
[0067] In the road surface structure of the present invention, a topcoat layer may be provided as an additional layer above the hard protective layer in order to further enhance aesthetics, weather resistance, and stain resistance. The topcoat layer can be formed using various conventionally known topcoat agents. The thickness of the topcoat layer can be appropriately selected depending on the properties of the topcoat agent used, but since the purpose is to provide aesthetics, weather resistance, and stain resistance, it is not necessary to make it a particularly thick film, and a thin film is preferable from a cost standpoint, and is specifically selected from a range of about 100 μm to 600 μm.
[0068] The road surface structure of the present invention is characterized by forming a water-based rigid urethane cement material that can be applied on a generally soft waterproof layer, and is suitably applied mainly to multi-story parking garages and rooftop parking garages where vehicles travel.
[0069] According to the road surface structure of the present invention, even when installed on a soft waterproof layer in an outdoor multi-story parking garage, it is less prone to defects such as warping, and it has durability against repeated vehicle traffic, turning of tires while parked, and vehicle traffic with snow chains attached during snowfall, thus maintaining waterproof performance over a long period of time. In particular, the water-based rigid urethane cement material, which is characteristic of the present invention and mainly uses aliphatic isocyanate resin, can significantly reduce curing shrinkage and greatly improve weather resistance.
[0070] According to the road surface structure of the present invention, by combining waterproof performance and durability for vehicle traffic, it is suitable as a waterproofing material for multi-story parking garages that use the rooftop as a parking area, which are often used in commercial facilities (department stores, mass retailers, etc.), theaters, restaurants, and other stores in urban areas where parking is scarce, and it is possible to protect the structure for a long period of time.
[0071] The embodiments described above are merely representative forms of the present invention, and the present invention is not limited to these embodiments. That is, the parties may implement the invention in various ways without departing from the core principles, in accordance with prior art. As long as such modifications still possess the configuration of the present invention, they are of course included within the scope of the present invention. [Examples]
[0072] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the following description, "parts" or "%" refers to mass unless otherwise specified.
[0073] According to the formulations shown in Table 1 below (Formulation Examples 1 to 5), each component was weighed into a 2-liter container so that the total mass was 1 kg. The mixture was then mixed for 1.5 minutes using an electric mixer at 600 rpm to prepare a water-based rigid urethane cement material.
[0074] [Table 1]
[0075] (Note 1) "ADEKA New Coat UCA-726-1" manufactured by ADEKA Corporation (viscosity: 120 mPa·s / 25 degrees, solids content: 55%) (Note 2) "Duranate TKA-100" manufactured by Asahi Kasei Corporation (NCO content g / 100g; 22.5~24.0) (Note 3) BASF INOAC Polyurethane Co., Ltd. "Luplanate M20S" (NCO content g / 100g; 30.0~32.5) (Note 4) "White Cement" manufactured by Taiheiyo Cement Corporation (Note 5) Ceramic material for insulating between the electric wire and its support. Particle size: 0.3 - 3.0 mm (Note 6) Manufactured by Tohoku Silica Sand Co., Ltd., mixed at a ratio of silica sand No. 4: silica sand No. 5 = 1:1 (mass ratio) (Note 7) "BYK - 054" manufactured by BYK Chemie Japan Co., Ltd.
[0076] (Example 1) Apply 0.8 kg / m of Atomrise JS, an acrylic rubber - based waterproof material manufactured by Atomix Co., Ltd., to the substrate (hereinafter simply referred to as "substrate"). Immediately paste Balance (reinforcing fabric) manufactured by Atomix Co., Ltd. After curing at 23°C for 3 hours, apply Atomrise JS again at 0.3 kg / m 2 After curing at 23°C for 24 hours, apply 12 kg / m of the aqueous rigid urethane - based cement material of Formulation Example 1 2 2
[0077] (Example 2) Apply 0.8 kg / m of Atomrise JS, an acrylic rubber - based waterproof material manufactured by Atomix Co., Ltd., to the substrate. Immediately paste Balance (reinforcing fabric) manufactured by Atomix Co., Ltd. After curing at 23°C for 3 hours, apply Atomrise JS again at 0.3 kg / m 2 After curing at 23°C for 24 hours, apply 10 kg / m of the aqueous rigid urethane - based cement material of Formulation Example 2 2 2
[0078] (Example 3) Apply 0.8 kg / m of Atomrise JS, an acrylic rubber - based waterproof material manufactured by Atomix Co., Ltd., to the substrate. Immediately paste Balance (reinforcing fabric) manufactured by Atomix Co., Ltd. After curing at 23°C for 3 hours, apply Atomrise JS again at 0.3 kg / m 2 After curing at 23°C for 24 hours, apply 11 kg / m of the aqueous rigid urethane - based cement material of Formulation Example 3 2 2
[0079] (Example 4) The base material is Atrane U60 Super, a urethane rubber-based waterproofing material manufactured by Atomix Co., Ltd., at a rate of 1.5 kg / m². 2 After application and curing at 23°C for 3 hours, apply Atrayne U60 Super again at a rate of 1.5 kg / m². 2 The surface was applied. After curing at 23°C for 24 hours, 12 kg / m² of the water-based rigid urethane cement material from Mixture Example 1 was added. 2 It was applied.
[0080] (Example 5) The base material is Atrane U60 Super, a urethane rubber-based waterproofing material manufactured by Atomix Co., Ltd., at a rate of 1.5 kg / m². 2 After application and curing at 23°C for 3 hours, apply Atrayne U60 Super again at a rate of 1.5 kg / m². 2 The coating was applied. After curing at 23°C for 24 hours, 12 kg / m² of the water-based rigid urethane cement material from Mixture Example 3 was added. 2 It was applied.
[0081] (Example 6) The base material is coated with 1.0 kg / m² of Atomix Co., Ltd.'s Substrate Adjustment Material A, a polymer cement waterproofing material. 2 Applied (total application amount 1.0 kg / m²) 2 After curing at 23°C for 24 hours, add 12 kg / m of the water-based rigid urethane cement material from Mixture Example 2. 2 It was applied.
[0082] (Example 7) The base material is coated with 1.0 kg / m² of Atomix Co., Ltd.'s Substrate Adjustment Material A, a polymer cement waterproofing material. 2 Applied (total application amount 1.0 kg / m²) 2 After curing at 23°C for 24 hours, add 12 kg / m of the water-based rigid urethane cement material from Mixture Example 2. 2 It was applied.
[0083] (Comparative Example 1) The base material is AtomRaise JS, an acrylic rubber-based waterproofing material manufactured by Atomix Co., Ltd., at a rate of 0.8 kg / m². 2 After application, immediately attach Atomix Corporation's Volance (reinforcement cloth), cure at 23°C for 3 hours, and then apply AtomRaise JS again at a rate of 0.3 kg / m².2 The coating was applied. After curing at 23°C for 24 hours, 12 kg / m² of the water-based rigid urethane cement material from Mixture Example 4 was added. 2 It was applied.
[0084] (Comparative Example 2) The base material is Atrane U60 Super, a urethane rubber-based waterproofing material manufactured by Atomix Co., Ltd., at a rate of 1.5 kg / m². 2 After application and curing at 23°C for 3 hours, apply Atrayne U60 Super again at a rate of 1.5 kg / m². 2 The coating was applied. After curing at 23°C for 24 hours, 12 kg / m² of the water-based rigid urethane cement material from Mixture Example 5 was applied. 2 It was applied.
[0085] (Comparative Example 3) The base material is AtomRaise JS, an acrylic rubber-based waterproofing material manufactured by Atomix Co., Ltd., at a rate of 0.8 kg / m². 2 After application, immediately attach Atomix Corporation's Volance (reinforcement cloth), cure at 23°C for 3 hours, and then apply AtomRaise JS again at a rate of 0.3 kg / m². 2 The coating was applied. After curing at 23°C for 24 hours, the coating material, obtained by mixing Toughmor, a high-strength epoxy floor coating material manufactured by Atomix Co., Ltd., and Silica Sand No. 6, manufactured by Tohoku Silica Sand Co., Ltd., in a mixing ratio of 1:6 (by mass), was applied at a rate of 12 kg / m². 2 It was applied.
[0086] (Comparative Example 4) The base material is Atrane U60 Super, a urethane rubber-based waterproofing material manufactured by Atomix Co., Ltd., at a rate of 1.5 kg / m². 2 After application and curing at 23°C for 24 hours, apply FloorTop U100NEO, a urethane rubber-based floor coating manufactured by Atomix Co., Ltd., at a rate of 1.0 kg / m². 2 After application and curing at 23°C for 24 hours, apply Floor Top U100NEO at a rate of 1.0 kg / m². 2 It was applied. Furthermore, FloorTop U100NEO, manufactured by Atomix Co., Ltd., is a hard urethane resin coating and is generally used as a floor coating material for the floors of machine shops and similar facilities.
[0087] [Evaluation Method] 1. Pressure wear test A standard concrete slab (300 x 300 x 60 mm) as specified in JIS A5371 Annex B was used as the base material, and one side was coated according to the specifications of the above examples and comparative examples. After curing at 23°C for 7 days, a pressure abrasion resistance test was conducted using this as a test plate.
[0088] The pressure abrasion test involved placing a test plate on a pressure abrasion testing machine (NKA-186, manufactured by Nikken Co., Ltd.), pressing the contact surface of a 50mm wide, 300mm diameter urethane rubber wheel against the test plate, applying a load of approximately 785N (80kgf), and rotating the concrete block at a rotation speed of 30 revolutions per minute for 30 minutes. After the test, the surface condition of the test plate was observed and evaluated. The evaluation criteria for the pressure abrasion test are as follows. The results are summarized in Table 3 below. ○: In good condition with only minor wear visible on a very small portion of the surface (hard protective layer). △: Obvious wear is visible on the surface layer (hard protective layer). ×: The surface layer (hard protective layer) is severely worn away.
[0089] 2. Accelerated durability test The following tests were conducted using a test device fitted with actual tires under the specified conditions. This simulates the durability of a vehicle equipped with snow chains when driving through a multi-story parking garage during winter.
[0090] The same test plate described in section "1. Pressure Abrasion Test" was prepared and fixed onto the disc of the test apparatus. With the tire's contact surface pressed against the test plate, both the tire and the disc were rotated. At this time, the tire was shifted at a speed of one reciprocal motion in 120 seconds, with a width of ±45 mm from the center of the test piece, in a direction perpendicular to the direction of rotation of the tire at the tire's contact surface. This shifting motion generates torsional stress. This is an evaluation test that was mainly developed as a durability evaluation test for road marking paints. The test conditions for the accelerated durability test are summarized in Table 2 below.
[0091] [Table 2]
[0092] The evaluation criteria for the accelerated durability test are as follows. The results are summarized in Table 3 below. ○: In good condition with only minor wear visible on a very small portion of the surface (hard protective layer). △: Obvious wear is visible on the surface layer (hard protective layer). ×: The surface layer (hard protective layer) is severely worn away.
[0093] 3. Weather resistance test A 70 x 150 x 3 mm slate board was used as the base material, and one side was coated according to the specifications of the above examples and comparative examples. After curing at 23°C for 7 days, a weather resistance test was conducted using this as a test board. The weathering test was conducted for 10 hours in accordance with the test method specified in JIS K 5600 7-7 "Accelerated weathering and accelerated lightfastness (xenon lamp method)".
[0094] After a 10-hour durability test, the color difference ΔE* was measured using a colorimeter. The evaluation criteria for the weather resistance test are as follows. The results are summarized in Table 3 below. ○:ΔE*≦5 △:5<ΔE*≦10 ×:10<ΔE*
[0095] 4. Warping Test This test evaluates the hardening shrinkage of a rigid protective layer made of water-based rigid urethane cement material, and confirms the effect of the rigid protective layer on the underlying waterproofing layer. A greater degree of warping indicates greater shrinkage.
[0096] SPTE (tinplate) sheets measuring 15.0 × 30.0 × 0.3 mm were used as the base material, and one side was coated according to the specifications of the above examples and comparative examples. The sheets were then placed on a horizontal surface and cured at 23°C for one month. After curing, the corners of the SPTE sheets were checked for warping, and if warping was observed, the height from the horizontal surface was measured. The evaluation criteria for the warping test are as follows. The results are summarized in Table 3 below. ○: The average height of the curve at the four corners is 10 mm or less. △: The average is between 10mm and 15mm. ×: The average exceeds 15mm.
[0097] 5. Repeated fatigue testing The repeated fatigue test evaluates the overall waterproofing performance of the road surface structure in each example and comparative example using the following method. A slate board measuring 70 x 150 x 3 mm was used as the base material, and one side was coated according to the specifications of the above examples and comparative examples. The board was then cured at 23°C for 7 days. After curing, the test was conducted according to the test method specified in "JASS 8 T-501-2014 Performance Evaluation Test Method for Membrane Waterproofing Layers 3.3 Fatigue Test". The evaluation criteria for the repeated fatigue test are as follows. The results are summarized in Table 3 below. 〇: Process 2-3 passed or higher. △: Passed up to process 2-1. ×: Process 1-3 or less.
[0098] [Table 3] [Industrial applicability]
[0099] The road surface construction method and road surface structure of the present invention were primarily developed for application to parking lot surfaces, but they can also be used for floors in food processing plants, machinery factories, and other similar applications where water-based rigid urethane cement materials are typically used. Therefore, the term "road surface" in this invention encompasses the floor surfaces of these factories as well.
Claims
1. a waterproof layer forming step of forming a waterproof layer on the road surface substrate, the waterproof layer being selected from the group consisting of an acrylic rubber coating waterproof layer, a urethane rubber coating waterproof layer, a PVC sheet waterproof layer, and a synthetic rubber sheet waterproof layer; a protective layer forming step of forming a hard protective layer directly or via an adhesive layer as an upper layer of the waterproof layer using an aqueous hard urethane cement material containing at least a polyol resin, an isocyanate resin, and a hydraulic cement; wherein the ratio of aliphatic isocyanate resin to all isocyanate resins contained in the aqueous rigid urethane cement material is 0.5 or more in terms of NCO equivalent ratio.
2. a waterproof layer formed on a road surface substrate, the waterproof layer being selected from the group consisting of an acrylic rubber coating waterproof layer, a urethane rubber coating waterproof layer, a PVC sheet waterproof layer, and a synthetic rubber sheet waterproof layer; a hard protective layer made of an aqueous hard urethane cement material laminated directly or via an adhesive layer as an upper layer of the waterproof layer; wherein the ratio of aliphatic isocyanate resin to all isocyanate resins contained in the aqueous rigid urethane cement material is 0.5 or more in terms of NCO equivalent ratio.